Analisis Motivasi Belajar Peserta Didik Melalui Pendekatan Kontekstual dalam Pembelajaran Geografi - Davin Valerian Dwiki Pratama Putra; Yuli Ifana Sari (Jurnal Ilmu Pendidikan, Sosial dan Humaniora, 2026)
This study seeks to examine the motivational factors that influence student engagement in geography education through a contextual framework at Setia Budi Christian High School, located in Malang City. This study uses a qualitative descriptive methodology, utilizing data collection techniques such as observation, interviews, and documentation. The findings show that the application of a contextual approach in geography education can significantly increase students' motivation to learn. Instructors skillfully connect educational content with students' real-world experiences, thereby fostering greater engagement in the educational process. However, certain elements, particularly student active participation in discussions and collaborative activities, require further improvement. The incorporation of media such as PowerPoint presentations and field research introduces diversity to the educational experience, making it more interesting and relevant to students' daily lives. The implications of this study underscore the need to maintain consistency in connecting academic material with actual phenomena surrounding students. In addition, encouraging increased collaboration within groups is also an important factor in strengthening student engagement and motivation to learn. This study significantly contributes to the evolution of effective contextual learning strategies that aim to increase student motivation and understanding of geographic content.